Using mHealth strategies in a Diabetes Management Program to improve the quality of care in Argentina: Study design and baseline data - Santero, Marilina (2018)
Aim: To evaluate the one-year post effect of the implementation of a diabetes program that includes mHealth interventions on the quality of diabetic care in public primary care centers. Method: It is a quasi-experimental study with outcome measurements at baseline, 6 and 12 months. The program includes primary care team training, a diabetes registry with a decision support tool in an app. and text messages for patients. Results: At baseline, 947 patients were included in the registry, 62.3% women with a mean age of 53.6 ± 11.5 years and 92% with type 2 diabetes. Common comorbidities were hypertension (61.3%) and obesity (59%). Only 16.9% had one HbA1c and 48.9% a cholesterol lab in the last year, 61.9% were screened for diabetic peripheral neuropathy, and 29.0% had one eye exam in the previous year. With respect to blood sugar, lipid and blood pressure control: 44.4% of those with HbA1c measurements had levels ≥8%, total cholesterol was over 200 mg/dL in 40.6% and 48.2% had uncontrolled blood pressure values. Conclusion: Patients with diabetes received a low quality of care at public primary care clinics. A diabetes registry allowed us to draw an epidemiological profile of diabetic patients and determine the quality of care provided.